(untitled) (Altre Modernità, 2012)
The paper discusses the fundamental characters of terminologies, with special reference to language science. The theory of language and linguistics put forth by Herman Paul (1846-1921) is then examined, focusing on the classification of sciences illustrated in the seminal theoretical essay of the German philologist, Prinzipien der Sprachgeschichte. The analysis of Paul’s work and of the terms used brings forth the implications of this classification, which aimed to give value to linguistics under a new historical perspective. The paper then considers the English translation of Paul’s Prinzipien, showing the difficulties and the inconsistencies in the terminological choices. Only a comprehensive analysis of the theory and its terms can lead to a deeper understanding of their implications, and thus pave the way to more consistent and effective translation. However, as shown by the analysis of the title of the essay, some terms can challenge the translator to the point that it becomes necessary to privilege one of the components of meaning, and accept solutions that are far form perfect and homogeneous across different languages.